Microscopic theory of the extremely nonlinear terahertz response of semiconductors - Golde, D.; Kira, M.; Meier, Torsten; Koch, S.W. (physica status solidi (b))
The extreme nonlinear terahertz response of initially unexcited intrinsic semiconductor nanostructures is studied theoretically by solving extended semiconductor Bloch equations numerically. The coupled dynamics of intraband acceleration and multiphoton interband transitions leads to high-harmonic generation up to several tens of the exciting terahertz frequency. It is shown that the actual cut-off frequency is determined by the band structure and not by the excitation strength.

Photocurrents in semiconductor carbon nanotubes with spin-orbit interaction - Meier, Torsten; Liu, Hong; Duc, Huynh Thanh; Schumache, Stefan (75. Annual meeting of the DPG and combined DPG Spring meeting)
In recent years, single-walled carbon nanotubes (SWCNTs) have received widespread attention due to their perfect quasi-one-dimensional structure and unique physical properties, as well as their potential for applications. In the present work, we calculate the band structure of SWCNTs using an atomistic tight-binding model including spin-orbit interaction. We combine this approach with a many-particle calculation of the nonlinear optical response using multi-band semiconductor Bloch equations. We show that, for SWCNTs lacking inversion symmetry, the intrinsic spin-orbit interaction can give rise to single-color photoinduced charge and spin currents. In particular, we study the influence of excitonic effects on these photoinduced currents and draw the analogy to recent investigations on single-color injection of photocurrents in semiconductor quantum wells.

Analysis of multidimensional Fourier transform spectroscopy for semiconductors with a phenomenological level model - Meier, Torsten; Wiebeler, Christian; Reichelt, Matthias (75. Annual meeting of the DPG and combined DPG Spring meeting)
Optical two-dimensional Fourier transform spectroscopy has been used to study the properties of semiconductor nanostructures in four-wave-mixing like experiments. Applying a phenomenological level model, we numerically and analytically analyze the main features of excitonic and biexcitonic contributions in a semiconductor quantum well by solving the optical Bloch equations. The method is extended to three-dimensional Fourier transform spectroscopy to investigate a recent experiment.

Extreme nonlinear optics in semiconductors with shaped laser pulses - Meier, Torsten; Reichelt, Matthias; Walther, Andrea (75. Annual meeting of the DPG and combined DPG Spring meeting)
If a two-level system is excited with an intense light field of several times the Rabi frequency, the well-known Mollow triplets appear in the emitted radiation spectrum. We show that the pattern of the emission spectrum can be changed by using appropriately shaped laser pulses. The effect is also observable for a more realistic description of a semiconductor system.

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Anticrossing of Whispering Gallery Modes in microdisk resonators embedded in an anisotropic environment - Declair, S.; Meier, Cedrik; Meier, Torsten; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the behavior of Whispering Gallery Modes (WGMs) in circularly shaped resonators like microdisks, with diameters in the range of optical vacuum wavelengths. The microdisk is embedded in an uniaxial anisotropic dielectric environment. By changing the optical anisotropy, one obtains spectral tunability of the optical modes. The degree of tunability strongly depends on the radial (azimuthal) mode order M (N). As the modes approach each other spectrally, anticrossing is observed, leading to a rearrangement of the optical states.
Keywords: tet_topic_microdisk

Coherent control of a single exciton qubit by optoelectronic manipulation - Michaelis de Vasconcellos, S.; Gordon, S.; Bichler, M.; Meier, Torsten; Zrenner, Artur (Nature Photonics)
The coherent state manipulation of single quantum systems is a fundamental requirement for the implementation of quantum information processors. Exciton qubits are of particular interest for coherent optoelectronic applications, in particular due to their excellent coupling to photons. Until now, coherent manipulations of exciton qubits in semiconductor quantum dots have been performed predominantly by pulsed laser fields. Coherent control of the population of excitonic states with a single laser pulse, observed by Rabi oscillations, has been demonstrated by several groups using different techniques1,2,3. By using two laser pulses, more general state control can be achieved4, and coupling of two excitons has been reported5,6. Here, we present a conceptually new approach for implementing the coherent control of an exciton two-level system (qubit) by means of a time-dependent electric interaction. The new scheme makes use of an optical clock signal and a synchronous electric gate signal, which controls the coherent manipulation.

Modeling excitonic line shapes in weakly disordered semiconductor nanostructures - Kuznetsova, I.; Gőgh, N.; Förstner, Jens; Meier, Torsten; Cundiff, S. T.; Varga, I.; Thomas, P. (Physical Review B)
Excitonic spectra of weakly disordered semiconductor heterostructures are simulated on the basis of a one-dimensional tight-binding model. The influence of the length scale of weak disorder in quantum wells on the redshift of the excitonic peak and its linewidth is studied. By calculating two-dimensional Fouriertransform spectra we are able to determine the contribution of disorder to inhomogeneous and also to homogeneous broadenings separately. This disorder-induced dephasing is related to a Fano-type coupling and leads to contributions to the homogeneous linewidth that depends on energy within the inhomogeneously broadened line. The model includes heavy- and light-hole excitons and yields smaller inhomogeneous broadening for the light-hole exciton if compared to the heavy-hole exciton, which agrees qualitatively with the experiment.
Keywords: tet_topic_qw

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
GaAs-based semiconductor microdisks with high quality whispering gallery modes (Q44000) have been fabricated.A layer of self-organized InAs quantumdots (QDs) served as a light source to feed the optical modes at room temperature. In order to achieve frequency tuning of the optical modes, the microdisk devices have been immersed in 4 – cyano – 4´-pentylbiphenyl (5CB), a liquid crystal(LC) with a nematic phase below the clearing temperature of TC≈34°C .We have studied the device performance in the temperature rangeof T=20-50°C, in order to investigate the influence of the nematic–isotropic phase transition on the optical modes. Moreover,we havea pplied an AC electric field to the device,which leads in the nematic phase to a reorientation of the anisotropic dielectric tensor of the liquid crystal.This electrical anisotropy can be used to achieve electrical tunability of the optical modes.Using the finite-difference time domain (FDTD) technique with an anisotropic material model, we are able to describe the influence of the liquid crystal qualitatively.
Keywords: tet_topic_qd; tet_topic_microdisk

Reversal of Coherently Controlled Ultrafast Photocurrents by Band Mixing in Undoped GaAs Quantum Wells - Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Physical Review Letters)
It is demonstrated that valence-band mixing in GaAs quantum wells tremendously modifies electronic transport. A coherent control scheme in which ultrafast currents are optically injected into undoped GaAs quantum wells upon excitation with femtosecond laser pulses is employed. An oscillatory dependence of the injection current amplitude and direction on the excitation photon energy is observed. A microscopic theoretical analysis shows that this current reversal is caused by the coupling of the light- and heavy-hole bands and that the hole currents dominate the overall current response. These surprising consequences of band mixing illuminate fundamental physics as they are unique for experiments which are able to monitor electronic transport resulting from carriers with relatively large momenta.
Keywords: tet_topic_qw

Enhanced FDTD edge correction for nonlinear effects calculation - Classen, C; Förstner, Jens; Meier, Torsten; Schuhmann, R (2010 IEEE Antennas and Propagation Society International Symposium)
The electromagnetic field in the vicinity of sharp edges needs a special treatment in numeric calculation whenever accurate, fast converging results are necessary. One of the fundamental works concerning field singularities has been proposed in 1972 [1] and states that the electromagnetic energy density must be integrable over any finite domain, even if this domain contains singularities. It is shown, that the magnetic field H(, ϕ) and electric field E(, ϕ) are proportional to ∝ (t−1) for → 0. The variable is the distance to the edge and t has to fulfill the integrability condition and thus is restricted to 0 < t < 1. This result is often used to reduce the error corresponding to the singularity without increasing the numerical effort [2 - 5]. For this purpose, a correction factor K is estimated by inserting the proportionality into the wave equation. It is shown, that this method improves the accuracy of the result significantly, however the order of convergence is often not studied. In [4] a method to modify the material parameters in order to use analytic results to improve the numeric calculation is presented. In this contribution we will - inspired by the scheme given in [4] - develop a new method to estimate a correction factor for perfect conducting materials (PEC) and demonstrate the improvement of the results compared to the standard edge correction. Therefore analytic results (comparable to [1]) are consequently merged with the scheme in [4]. The main goal of this work is the calculation of the second harmonic generation (SHG) in the wave response of so-called metamaterials [6]. Frequently these structures contain sharp metallic edges with field singularities at the interfaces which have a strong impact on the SHG signals. Thus, an accurate simulation of singularities is highly important. However, the following approach can also be applied to many other setups, and one of them is shown in the example below.
Keywords: tet_topic_numerics

Tuning quantum-dot based photonic devices with liquid crystals - Piegdon, Karoline A.; Declair, Stefan; Förstner, Jens; Meier, Torsten; Matthias, Heiner; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel; Meier, Cedrik (Optics Express)
Microdisks made from GaAs with embedded InAs quantum dots are immersed in the liquid crystal 4-cyano-4’-pentylbiphenyl (5CB). The quantum dots serve as emitters feeding the optical modes of the photonic cavity. By changing temperature, the liquid crystal undergoes a phase transition from the isotropic to the nematic state, which can be used as an effective tuning mechanism of the photonic modes of the cavity. In the nematic state, the uniaxial electrical anisotropy of the liquid crystal molecules can be exploited for orienting the material in an electric field, thus externally controlling the birefringence of the material. Using this effect, an electric field induced tuning of the modes is achieved. Numerical simulations using the finite-differences time-domain (FDTD) technique employing an anisotropic dielectric medium allow to understand the alignment of the liquid crystal molecules on the surface of the microdisk resonator.
Keywords: tet_topic_qd; tet_topic_microdisk

Coherently controlled electrical currents at surfaces - Güdde, J.; Rohleder, M.; Meier, Torsten; Koch, S.W.; Höfer, U. (Dynamics at Solid State Surfaces and Interfaces)

Microscopic analysis of charge and spin photocurrents injected by circularly polarized one-color laser pulses in GaAs quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Physical Review B)
The dynamics of charge and spin injection currents excited by circularly polarized, one-color laser beams in semiconductor quantum wells is analyzed. Our microscopic approach is based on a 14x14 k · p band-structure theory in combination with multisubband semiconductor Bloch equations which allows a detailed analysis of the photogenerated carrier distributions and coherences in k space. Charge and spin injection currents are numerically calculated for [110]- and [001]-grown GaAs quantum wells including dc population contributions and ac contributions that arise from intersubband coherences. The dependencies of the injection currents on the excitation conditions, in particular, the photon energy are computed and discussed.
Keywords: tet_topic_qw

Ultrafast coherent control of electric currents at metal surfaces - Güdde, J.; Rohleder, M.; Meier, Torsten; Koch, S.W.; Höfer, U. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIV)
We report the development of an experimental technique to measure the dynamics of electrical currents on the femtosecond timescale. The technique combines methods of coherent control with time- and angle-resolved photoelectron spectroscopy. Direct snapshots of the momentum distribution of the excited electrons as function of time are then determined by photoelectron spectroscopy. In this way we gain information on the generation and decay of ultrashort current pulses in unprecedented detail. In particular, this technique allows the observation of elastic electron scattering in terms of an incoherent population dynamics in momentum space. We have applied this optical current generation and detection scheme to electrons in so-called image-potential states which represent a prototype of two-dimensional electronic surface states. Electrons in these states are bound perpendicular to the metal surface by the Coulombic image potential whereas they can move almost freely parallel to the surface. For the (n=1) image-potential state of Cu(100) we find a decay time of 10 fs due to electron scattering with steps and surface defects.

Microscopic theoretical analysis of optically generated injection currents in semiconductor quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIV)
A microscopic theory that describes injection currents in GaAs quantum wells is presented. 14 × 14 band k.p theory is used to compute the band structure including anisotropy and spin-orbit interaction. Transient injection currents are obtained via numerical solutions of the semiconductor Bloch equations. Depending on the growth direction of the considered quantum well system and the propagation and polarization directions of the incident light beam, it is possible to generate charge and/or spin photocurrents on ultrashort time scales. The dependence of the photocurrents on the excitation conditions is computed and discussed.
Keywords: tet_topic_qw

Numerical Analysis of Coupled Photonic Crystal Cavities - Meier, Torsten; Declair, S.; Förstner, J. (AIP Conference Proceedings)
We present an analysis of the coupling between photonic crystal cavities in different geometries. Inline‐, side‐ and angle‐coupled L3‐geometries are investigated numerically in three dimensions. Asymmetric mode splitting of the fundamental mode for the L3‐cavity is shown for all geometrical setups evidencing for strong cavity‐cavity interactions. The coupling efficiency for the fundamental mode is shown to be best for a 30° angle between the cavity‐centers due to the direction of in‐plane leackage out of the cavites.

Localization of excitons in weakly disordered semiconductor structures: A model study - Gögh, N.; Thomas, P.; Kuznetsova, I.; Meier, Torsten; Varga, I. (Annalen der Physik)
We discuss transport and localization properties on the insulating side of the disorder dominated superconductor-insulator transition, described in terms of the dirty boson model. Analyzing the spectral properties of the interacting bosons in the absence of phonons, we argue that the Bose glass phase admits three distinct regimes. For strongest disorder the boson system is a fully localized, perfect insulator at any temperature. At smaller disorder, only the low temperature phase exhibits perfect insulation while delocalization takes place above a finite temperature. We argue that a third phase must intervene between these perfect insulators and the superconductor. This conducting Bose glass phase is characterized by a mobility edge in the many body spectrum, located at finite energy above the ground state. In this insulating regime purely electronically activated transport occurs, with a conductivity following an Arrhenius law at asymptotically low temperatures, while a tendency to superactivation is predicted at higher T. These predictions are in good agreement with recent transport experiments in highly disordered films of superconducting materials.

Localization of excitons in weakly disordered semiconductor structures: A model study - Gögh, N.; Thomas, P.; Kuznetsova, I.; Meier, Torsten; Varga, I. (Annalen der Physik)
We discuss transport and localization properties on the insulating side of the disorder dominated superconductor-insulator transition, described in terms of the dirty boson model. Analyzing the spectral properties of the interacting bosons in the absence of phonons, we argue that the Bose glass phase admits three distinct regimes. For strongest disorder the boson system is a fully localized, perfect insulator at any temperature. At smaller disorder, only the low temperature phase exhibits perfect insulation while delocalization takes place above a finite temperature. We argue that a third phase must intervene between these perfect insulators and the superconductor. This conducting Bose glass phase is characterized by a mobility edge in the many body spectrum, located at finite energy above the ground state. In this insulating regime purely electronically activated transport occurs, with a conductivity following an Arrhenius law at asymptotically low temperatures, while a tendency to superactivation is predicted at higher T. These predictions are in good agreement with recent transport experiments in highly disordered films of superconducting materials.

Experimental and theoretical investigations of photocurrents in non-centrosymmetric semiconductor quantum wells - Meier, Torsten; Duc, Huynh Thanh; Foerstner, Jens; Priyadarshi, S.; Racu, Ana Maria; Pierz, Klaus; Siegner, Uwe; Bieler, Mark (DPG Spring meeting 2010)
We compute photocurrents generated by femtosecond single-color laser pulses in non-centrosymmetric semiconductor quantum wells by combining a 14 x 14 k.p band structure theory with multi-band semiconductor Bloch equations. The transient photocurrents are investigated experimentally by measuring the associated Terahertz emission. The dependencies of the photocurrent and the Terahertz emission on the excitation conditions are discussed for (110)-oriented GaAs quantum wells. The comparison between theory and experiment shows a good agreement.

A numerical adaptive wavelet approach to excitonic absorption spectra of disordered semiconductor nanostructures - Meier, Torsten; Mollet, Christian; Kunoth, Angela (DPG Spring meeting 2010)
Semiconductor nanostructures always contain a certain degree of disorder due to interface roughness and/or alloy disorder. The disorder has significant influence on the optical properties, e.g., excitonic absorption spectra. An adaptive wavelet approach for the solution of the excitonic Schroedinger equation, i.e., the semiconductor Bloch equation for the interband coherence linear in the external field, has been developed and applied to compute absorption spectra and/or wave functions. Results obtained for a thin GaAs semiconductor quantum wire considering a number of different model disorder potentials are presented and discussed.

Controlling the third-harmonic generation in a metallic photonic crystal coupled to a waveguide - Meier, Torsten; Podzimski, Reinold; Reichelt, Matthias; Utikal, Tobias; Giessen, Harald (DPG Spring meeting 2010)
The behavior of waveguide plasmon polaritons is studied employing ultrafast coherent control like schemes for a gold lattice coupled to a photonic waveguide for the structure. Different models to describe the third-harmonic generation are presented and the resulting equations are solved numerically. The calculations are compared to recent experimental data and show good agreement for the most prominent features in the time-integrated third order intensity.

Theoretical description of optical properties in III-V semiconductor nanostructures - Meier, Torsten; Landmann, Marc; Pochwala, Michal; Foerstner, Jens; Rauls, Eva; Schmidt, Wolf Gero (DPG Spring meeting 2010)
We present a joint theoretical study of the optical properties of GaAs and AlAs bulk and heterostructures. Thereby, we compare the theoretical description of optical excitation on several levels of theory. Results obtained from kp theory are discussed along with data from ab initio calculations within the frameworks of independent-particle (DFT), independent quasiparticle (GW), or Coulomb-correlated quasiparticle (BSE) approximation.

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Ultrafast Coherent Interactions in Quantum Wells Studied by Two-Dimensional Fourier Transform Spectroscopy - Meier, Torsten; Zhang, Tianhao; Kuznetsova, Irina; Yang, Lijun; Bristow, Alan D; Dai, Xingcan; Li, Xiaoqin; Thomas, P.; Mukamel, S.; Mirin, Richard P.; Cundiff, S.T. (Ultrafast Phenomena XVI: Proceedings of the 16th International Conference, Palazzo dei Congressi Stresa, Italy, June 9--13, 2008)

Generation and time‐resolved detection of coherently controlled electric currents at surfaces - Meier, Torsten; Güdde, Jens; Rohleder, M.; Koch, S.W.; Höfer, Ulrich (physica status solidi c)
We demonstrate a technique for the generation and detection of electron currents at surfaces on a femtosecond time scale with a contact-free experimental setup based on a combination of coherent control and photoemission spectroscopy. We have applied this technique for electrons excited into image-potential states on a Cu(100) surface that form a free-electron-like band in the direction parallel to the surface. The photogeneration of currents is described by optical Bloch equations for a multiband model. By incorporating field-induced interband and intersubband transitions together with intraband accelerations into the model, the observed phase dependence of the population and of the current can be reproduced.

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Coherent control in hybrid metal-semiconductor nanostructures - Meier, Torsten; Reichelt, Matthias (DPG Spring meeting 2009)
Recently it has been shown experimentally that it is possible to coherently control nano-optical excitations by using sophisticated shaped laser pulses. In this work a similar technique is used to theoretically investigate a hybrid nanostructure which consists of a metal aperture and a quantum wire. It is shown that one can concentrate the optically excited electron density at an arbitrary position due to wave packet dynamics by chosing particular frequency components and phases of the chirped laser pulse. The optimization process is performed with a genetic algorithm which is linked to a 3D-FDTD solver.

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Microscopic theory of the linear and nonlinear Terahertz response of semiconductors - Meier, Torsten; Koch, S.W.; Kira, M.; Steiner, J.T.; Golde, D. (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference)
The paper presents a theoretical analysis of the nonlinear THz response from the internal transitions of coherent and incoherent excitons based on the formulated microscopic THz theory. Moreover, the response of unexcited semiconductors to extremely intense THz fields is investigated .The intersubband transitions of optically excited quantum wells using linear THz spectroscopy is also studied. The computed differential transmission shows a characteristic Fano-like line shape of the intersubband resonance. The pure intersubband contribution is given by a simple Lorentzian. Applying the microscopic theory, the Fano features of the total response can be attributed to the phase-sensitive superposition of the intersubband transitions and the ponderomotive contribution. These results are in excellent agreement with recent experiments.

Ultrafast coherent photoelectron emission effects and their application for time-domain studies of current transport - Meier, Torsten; Koch, S.W.; Rohleder, M.; Gudde, J.; Hofer, U. (Conference on Lasers and Electro-Optics and 2009 Conference on Quantum electronics and Laser Science Conference)
By combining coherent control schemes and photoelectron spectroscopy it is possible to generate ultrafast current pulses at surfaces and in solids and to detect their decay directly in momentum space with femtosecond time resolution.

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

Preface - Meier, Torsten; Michler, Peter (physica status solidi c)

Photo-and spin current generation and dynamics in semiconductor nanostructures - Meier, Torsten; Duc, Huynh Thanh; Foerstner, Jens (DPG Spring meeting 2009)
The band structure and wave functions of GaAs quantum wells are computed via k.p band structure theory including anisotropy and spin splitting. Using these results, the process of generating photocurrents by optical excitation is analyzed. Depending on the symmetry of the material, the direction of the laser beam, and the polarization direction of the light field/s, one can coherently generate charge and/or spin photocurrents on ultrashort time scales. The direction, the strength, and the dynamics of these photocurrents are computed and discussed.

Direct determination of exciton homogeneous and inhomogeneous linewidths in semiconductor quantum wells with two-dimensional fourier transform spectroscopy - Meier, Torsten; Zhang, Tianhao; Bristow, Alan D.; Dai, Xingcan; Kuznetsova, Irina; Thomas, P.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Homogeneous and inhomogeneous broadening of heavy- and light-hole excitons in semiconductor quantum wells are measured along with the excitation dependence of both broadenings. Isolation of disorder-induced broadening is possible with spectra in different coherent pathways.

Intensity dependence of charge and spin currents generated by ultrafast two-color photoexcitation of semiconductor quantum wells - Meier, Torsten; Duc, Huynh Thanh; Koch, S.W.; Pasenow, B. (72nd annual meeting and DPG spring meeting of the Condensed Matter Section and the Divisions)

Influence of heavy-hole light-hole band mixing on the strength of optically generated spin-currents in III-V semiconductor quantum wells - Meier, Torsten; Koch, S.W.; Pasenow, B. (72nd annual meeting and DPG spring meeting of the Condensed Matter Section and the Divisions)

High harmonics generated in semiconductor nanostructures by the coupled dynamics of optical inter- and intraband excitations - Golde, D.; Meier, Torsten; Koch, S. W. (Physical Review B)
The emitted radiation from semiconductor nanostructures due to the excitation with intense ultrashort optical laser pulses is analyzed. Semiconductor Bloch equations that consistently describe the coupled light-field-induced interband and intraband dynamics are solved numerically. It is demonstrated that the intraband dynamics considerably influences the light emission in the regime of extreme nonlinear optics. In particular, the intraband acceleration significantly modifies the dynamics of the interband polarization which results in a strong enhancement of high-harmonic generation.

Microscopic Analysis of the Optical and Electronic Properties of Semiconductor Photonic-Crystal Structures - Meier, Torsten; Pasenow, B.; Reichelt, Matthias; Stroucken, T. (Nanophotonic Materials: Photonic Crystals, Plasmonics, and Metamaterials)

Generation and Time-Resolved Detection of Coherently Controlled Electric Currents at Surfaces - Güdde, J.; Rohleder, M.; Meier, Torsten; Koch, S.W.; Höfer, U. (Frontiers in Optics 2008/Laser Science XXIV/Plasmonics and Metamaterials/Optical Fabrication and Testing)

Ultrafast Dynamics of Optically-Induced Charge and Spin Currents in Semiconductors - Meier, Torsten; Duc, Huynh Thanh; Vu, Quang Tuyen; Pasenow, Bernhard; Hübner, Jens; Chatteryee, Sangam; Rühle, Wolfgang W.; Haug, Hartmut; Koch, Stephan W. (Advances in Solid State Physics)
The ultrafast dynamics of optical excitations in semiconductors and semiconductor nanostructures can be computed on a microscopic theoretical basis using the semiconductor Bloch equations. This set of equations allows one to nonperturbatively evaluate light-field-induced intraband and interband excitations and is also well suited for the analysis of many-body effects such as excitonic resonances and carrier-carrier and carrier-phonon scattering processes. In this article we start with a description of an experimental observation of coherent spin photocurrents, then we briefly introduce the theoretical approach and review some results of our theory concerning the microscopic description of the ultrafast coherent optical generation and the temporal decay of charge and spin currents in semiconductor nanostructures. The computed transients show an enhanced damping of the spin current relative to the charge current as a consequence of Coulomb scattering between carriers with opposite spin. The influence of quantum kinetic memory effects on the dynamics of the photocurrents is analyzed by evaluating the scattering terms beyond the Markov approximation.

Ultrafast Dynamics of Optically-Induced Charge and Spin Currents in Semiconductors - Meier, Torsten; Duc, Huynh Thanh; Vu, Quang Tuyen; Pasenow, Bernhard; Hübner, Jens; Chatteryee, Sangam; Rühle, Wolfgang W.; Haug, Hartmut; Koch, Stephan W. (Advances in Solid State Physics)
The ultrafast dynamics of optical excitations in semiconductors and semiconductor nanostructures can be computed on a microscopic theoretical basis using the semiconductor Bloch equations. This set of equations allows one to nonperturbatively evaluate light-field-induced intraband and interband excitations and is also well suited for the analysis of many-body effects such as excitonic resonances and carrier-carrier and carrier-phonon scattering processes. In this article we start with a description of an experimental observation of coherent spin photocurrents, then we briefly introduce the theoretical approach and review some results of our theory concerning the microscopic description of the ultrafast coherent optical generation and the temporal decay of charge and spin currents in semiconductor nanostructures. The computed transients show an enhanced damping of the spin current relative to the charge current as a consequence of Coulomb scattering between carriers with opposite spin. The influence of quantum kinetic memory effects on the dynamics of the photocurrents is analyzed by evaluating the scattering terms beyond the Markov approximation.

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)

High harmonics generated in semiconductor nanostructures by the coupled dynamics of optical inter- and intraband excitations - Golde, D.; Meier, T.; Koch, S. W. (Physical Review B)

Modeling of the Extreme Nonlinear Optical Response of Semiconductor Nanostructures - Golde, D.; Meier, Torsten; Koch, S.W. (Ultrafast Phenomena XV: Proceedings of the 15th International Conference)
In extreme nonlinear optics the Rabi frequency is comparable to or even larger than the transition frequency. Numerical solutions of the semiconductor Bloch equations show that the response of semiconductor quantum wells and wires differs characteristically from that of a two-level system in this highly nonperturbative regime. The main reason for these differences is the continuous electronic dispersion, and, to a lesser degree, the Coulombic interaction effects.

Microscopic analysis of the optical and electronic properties of semiconductor photonic‐crystal structures - Pasenow, B.; Reichelt, Matthias; Stroucken, T.; Meier, Torsten; Koch, S.W. (physica status solidi (a))
The combination of dielectric photonic crystals and semiconductor nanostructures makes it possible to design many important aspects of the optoelectronic system response. A spatially-varying dielectric environment induces modifications of the transversal and the longitudinal components of the electromagnetic field which have to be included in the self-consistent microscopic analysis of the optical properties of hybrid semiconductor photonic-crystal structures. In this paper, the development of a semiclassical microscopic theory is reviewed. Whereas the classical electromagnetic field is described at the level of Maxwell's equations, a full many-body quantum theory is used for the interacting electronic excitations in the semiconductor material. Relevant examples of the numerical solutions of the resulting Maxwell semiconductor Bloch equations are presented showing, e.g., characteristic modifications of excitonic absorption spectra, the spatio-temporal dynamics of electronic wave packets, as well as an increase of the optical gain in properly designed device geometries.

Determination of homogeneous and inhomogeneous broadening in semiconductor nanostructures by two-dimensional Fourier-transform optical spectroscopy - Kuznetsova, I.; Meier, Torsten; Cundiff, S.T.; Thomas, P. (Physical Review B)
The imaginary part of two-dimensional Fourier-transform spectra in the rephasing and nonrephasing modes is used to analyze the homogeneous and inhomogeneous broadening of excitonic resonances in semiconductor nanostructures. Microscopic calculations that include heavy- and light-hole excitons as well as coherent biexcitonic many-body correlations reveal distinct differences between the rephasing and nonrephasing spectra. A procedure is proposed that allows separation of disorder-induced broadening in complex systems that show several coupled resonances.

Ultrafast dynamics of photoexcited charge and spin currents in semiconductor nanostructures - Meier, Torsten; Pasenow, B.; Duc, H.T.; Vu, Q.T.; Haug, H.; Koch, S.W. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XI and Semiconductor Photodetectors IV)
Employing the quantum interference among one- and two-photon excitations induced by ultrashort two-color laser pulses it is possible to generate charge and spin currents in semiconductors and semiconductor nanostructures on femtosecond time scales. Here, it is reviewed how the excitation process and the dynamics of such photocurrents can be described on the basis of a microscopic many-body theory. Numerical solutions of the semiconductor Bloch equations (SBE) provide a detailed description of the time-dependent material excitations. Applied to the case of photocurrents, numerical solutions of the SBE for a two-band model including many-body correlations on the second-Born Markov level predict an enhanced damping of the spin current relative to that of the charge current. Interesting effects are obtained when the scattering processes are computed beyond the Markovian limit. Whereas the overall decay of the currents is basically correctly described already within the Markov approximation, quantum-kinetic calculations show that memory effects may lead to additional oscillatory signatures in the current transients. When transitions to coupled heavy- and light-hole valence bands are incorporated into the SBE, additional charge and spin currents, which are not described by the two-band model, appear.

Investigation of Coulomb-induced coupling in semiconductor nanostructures using 2D Fourier-Transform-Spectroscopy - Meier, Torsten; Kuznetsova, Irina; Thomas, Peter; Zhang, Tianhao; Cundiff, Steven T. (International Quantum Electronics Conference)
Two-Dimensional Fourier-Transform-Spectroscopy (2DFTS) is a novel method for the experimental investigation of many-body interactions in semiconductor nanostructures [1]. It displays directly the heavy-hole (hh) and light-hole (lh) excitonic transitions in III-V-quantum wells along the main diagonal of a two-dimensional plot which is spanned by the excitation energy −ħωτ and the emission energy ħωτ. In addition, characteristic signatures due to continuum excitations appear as well as mixed peaks in off-diagonal positions resulting from various couplings. Using a one-dimensional tight-binding model which contains the correct selection rules we compute 2DFTS in the coherent χ(3)-limit. By comparing theoretical spectra resulting from different orders in the Coulomb interaction we can clearly identify the influence of the many-particle interaction on the various signatures that are visible in the spectrograms. The distribution of the peak heights, their magnitude, and their lineshape are of particular interest. Co-circularly polarized excitation pulses are considered.

Experimental and theoretical studies of exciton correlations using optical two-dimensional fourier transform spectroscopy - Meier, Torsten; Zhang, Tianhao; Li, Xiaoqin; Cundiff, S.T.; Mirin, R. P.; Kuznetsova, Irina; Thomas, P. (Quantum Electronics and Laser Science Conference)
Many-body correlations of excitons in semiconductors are explored experimentally with two-dimensional Fourier transform spectroscopy and modeled by a microscopic coherent χ(3) theory beyond the Hartree-Fock approximation with qualitative agreements under different excitation conditions.

Multidimensional ultrafast spectroscopy special feature: polarization-dependent optical 2d fourier transform spectroscopy of semiconductors - Meier, Torsten; Zhang, Tianhao; Kuznetsova, Irina; Li, Xiaoqin; Mirin, R. P.; Thomas, Peter; Cundiff, S.T. (Proceedings of the National Academy of Sciences)
Optical 2D Fourier transform spectroscopy (2DFTS) provides insight into the many-body interactions in direct gap semiconductors by separating the contributions to the coherent nonlinear optical response. We demonstrate these features of optical 2DFTS by studying the heavy-hole and light-hole excitonic resonances in a gallium arsenide quantum well at low temperature. Varying the polarization of the incident beams exploits selection rules to achieve further separation. Calculations using a full many-body theory agree well with experimental results and unambiguously demonstrate the dominance of many-body physics.

Coherent Semiconductor Optics - Meier, Torsten; Thomas, Peter; Koch, Stephan W.

Microscopic modeling of photoluminescence of strongly disordered semiconductors - Bozsoki, P.; Kira, M.; Hoyer, W.; Meier, Torsten; Varga, I.; Thomas, P.; Koch, S.W. (Journal of Luminescence)
A microscopic theory for the luminescence of ordered semiconductors is modified to describe photoluminescence of strongly disordered semiconductors. The approach includes both diagonal disorder and the many-body Coulomb interaction. As a case study, the light emission of a correlated plasma is investigated numerically for a one-dimensional two-band tight-binding model. The band structure of the underlying ordered system is assumed to correspond to either a direct or an indirect semiconductor. In particular, luminescence and absorption spectra are computed for various levels of disorder and sample temperature to determine thermodynamic relations, the Stokes shift, and the radiative lifetime distribution.

Signatures of Many-Particle Correlations in Two-Dimensional Fourier-Transform Spectra of Semiconductor Nanostructures - Kuznetsova, I.; Thomas, P.; Meier, Torsten; Zhang, T.; Li, X.; Mirin, R.P.; Cundiff , S. T. (Solid state communications)
On the basis of a microscopic theory, the signatures of many-particle correlations in Two-Dimensional Fourier-Transform Spectra (2D-FTS) of semiconductor nanostructures are identified and compared to experimental data. Spectra in the photon energy range of the heavy-hole and light-hole excitonic resonances show characteristic features due to correlations, which depend on the relative polarization directions of the excitation pulses.

Polarization-dependent optical 2D Fourier transform spectroscopy of semiconductors - Meier, Torsten; Cundiff, S.T.; Zhang, T.; Li, X.; Bristow, A. D.; Kuznetsova, I.; Thomas, P.; Yang, L.; Schweigert, I. V.; Mukamel, S.; Mirin, R. P. (Laser Science XXIII Organic Materials and Devices for Displays and Energy Conversion)
Optical two dimensional Fourier transform spectra of excitonic resonances in semiconductors are measured and calculated. They provide insight into many-body interactions in direct gap semiconductors by separating the contributions to the coherent optical nonlinear response.

Time-Resolved Investigation of Coherently Controlled Electric Currents at a Metal Surface - Gudde, J.; Rohleder, M.; Meier, Torsten; Koch, S. W.; Hofer, U. (Science)
Studies of current dynamics in solids have been hindered by insufficiently brief trigger signals and electronic detection speeds. By combining a coherent control scheme with photoelectron spectroscopy, we generated and detected lateral electron currents at a metal surface on a femtosecond time scale with a contact-free experimental setup. We used coherent optical excitation at the light frequencies ωa and ωa/2 to induce the current, whose direction was controlled by the relative phase between the phase-locked laser excitation pulses. Time- and angle-resolved photoelectron spectroscopy afforded a direct image of the momentum distribution of the excited electrons as a function of time. For the first (n = 1) image-potential state of Cu(100), we found a decay time of 10 femtoseconds, attributable to electron scattering with steps and surface defects.

Polarization-dependent optical 2D Fourier transform spectroscopy of semiconductors - Zhang, T.; Kuznetsova, I.; Meier, Torsten; Li, X.; Mirin, R. P.; Thomas, P.; Cundiff, S. T. (Proceedings of the National Academy of Sciences (PNAS))
Optical 2D Fourier transform spectroscopy (2DFTS) provides insight into the many-body interactions in direct gap semiconductors by separating the contributions to the coherent nonlinear optical response. We demonstrate these features of optical 2DFTS by studying the heavy-hole and light-hole excitonic resonances in a gallium arsenide quantum well at low temperature. Varying the polarization of the incident beams exploits selection rules to achieve further separation. Calculations using a full many-body theory agree well with experimental results and unambiguously demonstrate the dominance of many-body physics.

Aspects of heavy-hole light-hole band mixing effects on the coherent optical generation of charge and spin currents in semiconductor heterostructures - Meier, Torsten; Pasenow, B.; Koch, S.W.; Duc, Huynh Thanh (71. Annual meeting 2007 and DPG-spring meeting of the division condensed matte)
The coherent optical injection and temporal decay of spin and charge currents in semiconductor heterostructures has be described on a microscopic basis including Coulomb and phononic effects up to the level of second-order Born contributions. In this talk the previously used two-band effective mass approach is extended to a multi-band approach using realistic microscopic kp matrix elements. Furthermore, the influence of heavy-hole light-hole band-mixing contained in the kp calculation and its effects on the microscopic semiconductor dynamics is demonstrated and discussed.

Optical Experiments on Second-Harmonic Generation with Metamaterials Composed of Split-Ring Resonators - Klein, Matthias W.; Enkrich, Christian; Wegener, Martin; Förstner, Jens; Moloney, Jerome V.; Hoyer, Walter; Stroucken, Tineke; Meier, Torsten; Koch, Stephan W.; Linden, Stefan (Photonic Metamaterials: From Random to Periodic)
We study optical second-harmonic generation from planar arrays of magnetic split-ring resonators at 1.5 microns resonance wavelength. We obtain by far the largest signals when exciting the magnetic-dipole resonance.
Keywords: tet_topic_meta

Microscopic Theory of Coherent Semiconductor Optics - Meier, Torsten; Koch, S.W. (Quantum Coherence: From Quarks to Solids)
The derivation of a microscopic many-body theory for the nonlinear optical response of semiconductors is reviewed. At the Hartree–Fock level, the semiconductor Bloch equations include many-body effects via band gap and field renormalization. These equations are sufficient to describe excitonic resonances as they appear already in the linear absorption spectra. An adequate description of nonlinear optical effects in semiconductors beyond the Hartree–Fock level includes Coulomb interaction induced carrier correlations. Different schemes have been developed to treat such correlation effects. As two examples, the second-order Born approximation and the dynamics-controlled truncation scheme are introduced and analyzed. In addition to the derivation of the equations of motion, a few examples are presented which highlight important signatures of many-body correlations in the optical response of semiconductors.

Microscopic analysis of extreme nonlinear optics in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (Journal of the Optical Society of America B)
A microscopic analysis is presented for the extreme nonlinear optical response of semiconductor quantum wells and wires after intense excitation with femtosecond laser pulses. In this regime, the light–matter interaction is the dominant eneregy scale, leading to a number of interesting effects such as carrier-wave Rabi flopping, Mollow splitting, and the creation of higher harmonics. The results presented here were obtained by evaluating the semiconductor Bloch equations without the rotating wave approximation. The electronic dispersion of semiconductor nanostructures is shown to have a characteristic influence on the extreme nonlinear optical response, whereas the relative importance of the carrier Coulomb interaction decreases with increasing excitation intensities.

Characterization of Disorder in Semiconductors via Single-Photon Interferometry - Bozsoki, P.; Thomas, P.; Kira, M.; Hoyer, W.; Meier, Torsten; Koch, S. W.; Maschke, K.; Varga, I.; Stolz, H. (Physical Review Letters)
The method of angular photonic correlations of spontaneous emission is introduced as an experimental, purely optical scheme to characterize disorder in semiconductor nanostructures. The theoretical expression for the angular correlations is derived and numerically evaluated for a model system. The results demonstrate how the proposed experimental method yields direct information about the spatial distribution of the relevant states and thus on the disorder present in the system.

Microscopic Many-Body Analysis of Ultrafast Photocurrents in Semiconductor Nanostructures - Meier, Torsten; Vu, Q.T.; Duc, H.T.; Pasenow, B.; Haug, H.; Koch, S.W. (International Conference on Ultrafast Phenomena XV)
The dynamics of charge and spin currents generated by two-color femtosecond laser pulses is investigated. Non-Markovian memory effects lead to oscillations in the coherent transients. Consequences arising from the heavy-hole light-hole coupling are predicted.

Microscopic modeling of the optical properties of semiconductor nanostructures - Thränhardt, A.; Meier, Torsten; Reichelt, Matthias; Schlichenmaier, C.; Pasenow, B.; Kuznetsova, I.; Becker, S.; Stroucken, T.; Hader, J.; Zakharian, A.R.; Moloney, J.V.; Chow, W.W.; et al. (Journal of Non-Crystalline Solids)
A brief overview of a consistent microscopic approach to model the optical and electronic properties of semiconductor nanostructures is presented. Coupled semiconductor Bloch and Maxwell equations are used to investigate the performance of semiconductor microcavity structures, photonic band gap systems, and lasers. The predictive potential of the microscopic theory is demonstrated for several examples of practical importance. Optical gain and output characteristics are computed for modern vertical external cavity surface emitting laser structures. It is shown how design flexibilities can be used to optimize the device performance. Nanostructures are proposed where semiconductor quantum wells are embedded in one-dimensional photonic crystals. For field modes spectrally below the photonic band edge it is shown that the optical gain and absorption can be enhanced by more than one order of magnitude over the value of the homogeneous medium. The increased gain can be used for laser action by placing quantum wells and a suitably designed photonic crystal structure inside a microcavity.

Temporal decay of coherently optically injected charge and spin currents due to carrier–LO-phonon and carrier-carrier scattering - Duc, H. T.; Vu, Q. T.; Meier, Torsten; Haug, H.; Koch, S. W. (Physical Review B)
The coherent ultrafast optical injection and the temporal evolution of charge and spin currents in semiconductors is analyzed using a microscopic many-body theory. The approach is based on the semiconductor Bloch equations and includes light-field-induced intraband and interband excitations, excitonic effects, and carrier–LO-phonon and carrier-carrier scattering processes. The relaxation effects are treated both in the second Born-Markov approximation and on the level of quantum kinetic theory including memory effects. The dynamics of the charge and spin currents is evaluated numerically for a one-dimensional model system. The dependence of the currents and their decay on the temperature, the excitation intensities, and the frequencies of the incident light fields is discussed. Whereas the overall decay dynamics is described well within the Markov approximation, the quantum kinetic theory predicts additional oscillatory signatures in the current transients.

Semiconductor Optics in Photonic Crystal Structures - Meier, Torsten; Koch, S.W. (Photonic Crystals: Advances in Design, Fabrication, and Characterization)

Computational Optoelectronics of Semiconductor Nanostructures including Many-Body Effects - Meier, Torsten; Duc, Huynh Thanh; Reichelt, Matthias; Pasenow, B.; Stroucken, T.; Koch, S.W. (Germany in NIC Series Vol. 32)
The linear and nonlinear optical properties of semiconductors are strongly influenced by the Coulomb interaction among the photoexcited carriers. Within the framework of the semiconductor Bloch equations such many-body effects can be described on the basis of a microscopic theory. In this article, we briefly review our recent contributions to two specific topics. First, the coherent optical generation of charge and spin currents and their subsequent decay via scattering processes is discussed. As a second example, the spatially-inhomogeneous optical properties of hybrid structures which consist of photonic crystals and semiconductor nanostructures are described. Many of the numerical results have been obtained using massively parallel computer programs which were run on the IBM p690-Cluster Jump in Jülich.

Type I type II transition in optical spectra-experiments and microscopic theory - Meier, Torsten; Schlichenmaier, C.; Thraenhardt, Angela; Koch, S.W.; Hantke, Kristian; Ruehle, Wolfgang; Gruening, Heiko; Klar, Peter J.; Heimbrodt, Wolfgang; Hader, J.; Moloney, Jerome V. (Meeting of the German Physical Society, Solid-State Physics Section, and the European Physical Society Condensed Matter Division)
The band alignment of GaNAs in heterostructures is determined by investigating the energetically lowest optical band-to-band transition of In0.23Ga0.77As/GaNyAs1−y samples with varying y. In a type II alignment this transition is between states located in different layers. Photoreflectance, photoluminescence, and the radiative decay of excited carrier densities are both measured and microscopically modeled. The bandstructure for every sample is computed. Based on this bandstructure all optical properties and the radiative decay are computed using the semiconductor Bloch [1] and luminescence [2] equations including electron-electron and electron-phonon interaction on scattering level. Thus the modeling is consistent and without free parameters. Overall good agreement between theory and experiment is achieved and used to explain all experimental features and to determine the band alignment

Microscopic analysis of extreme nonlinear optics in semiconductors - Meier, Torsten; Golde, Daniel; Koch, S.W. (Meeting of the German Physical Society, Solid-State Physics Section, and the European Physical Society Condensed Matter Division)
Extreme nonlinear optics denotes the regime where the Rabi frequency is comparable to or even larger than the band gap frequency. This regime can be reached experimentally by using intense ultrashort laser pulses which have a duration of just a few femtoseconds, see, e.g., [1]. As shown in [2] for the case of a two-level system, a theoretical analysis of extreme nonlinear optics requires one to describe the dynamics on ultrashort time scales beyond the rotating-wave approximation. Such calculations describe, e.g., the generation of higher harmonics and Mollow tripletts [1,2]. Here, we use a microscopic model of a two-band semiconductor with Coulomb interaction to analyze the regime of extreme nonlinear optics. It is, in particular, shown that the importance of excitonic effects which are known to dominate the nonlinear optical response at moderate excitation intensities become less important at largely elevated intensities

Coherent optical generation and decay of charge and spin currents in semiconductor heterostructures analyzed by microscopic theory - Meier, Torsten; Vu, Q.T.; Koch, S.W.; Duc, Huynh Thanh (Meeting of the German Physical Society, Solid-State Physics Section, and the European Physical Society Condensed Matter Division)

Extracting the Random potential of disordered semiconductors via directional interference of photoluminescence - Meier, Torsten; Bozsoki, Peter; Hoyer, W.; Kira, M.; Thomas, P.; Koch, S.W.; Maschke, K. (Meeting of the German Physical Society, Solid-State Physics Section, and the European Physical Society Condensed Matter Division)

Type I-type II transition in InGaAs–GaNAs heterostructures - Schlichenmaier, C.; Grüning, H.; Thränhardt, A.; Klar, P.J.; Kunert, B.; Volz, K.; Stolz, W.; Heimbrodt, W.; Meier, Torsten; Koch, S.W. (Applied Physics Letters)
Optical interband transitions in a series of In0.23Ga0.77As–GaN𝑥As1−𝑥 quantum well samples are investigated. For changing nitrogen content, a type I-type II transition is identified by a detailed analysis of photoluminescence and photoreflectance spectra. Experimental results are compared systematically with spectra calculated by a microscopic theory. A valence band offset parameter of (1.5±0.5)eV is extracted for this heterostructure system.This work was supported by the Deutsche Forschungsgemeinschaft (Research Group on Metastable Compound Semiconductors and Heterostructures), by AFOSR (F49620-02-1-0380) and the Max-Planck Research Prize of the Max-Planck Society and Humboldt Foundation. We thank Stanko Tomić (Daresbury Laboratory) for fruitful discussions.

Spatially inhomogeneous optical gain in semiconductor photonic-crystal structures - Reichelt, Matthias; Pasenow, B.; Meier, Torsten; Stroucken, T.; Koch, S.W. (Physical Review B)
The optical and electronic properties of semiconductor heterostructures in the vicinity of photonic crystals are discussed. The theoretical approach provides a self-consistent solution of the dynamics of the electromagnetic field and the material excitations. Due to the influence of the structured dielectric environment on the Coulomb interaction, the exciton resonances and the quasiequilibrium carrier densities in the spatially homogeneous semiconductor become space dependent. It is demonstrated that these inhomogeneities lead to distinct modifications of the optical absorption and gain spectra. As an application, numerically calculated density-dependent optical spectra are analyzed for an array of semiconductor quantum wires which are close to a two-dimensional photonic crystal. The spatial inhomogeneities result in novel excitonic absorption features and modification of the optical gain in these structures.

Enhanced light-matter interaction in semiconductor heterostructures embedded in one-dimensional photonic crystals - Pasenow, Bernhard; Reichelt, Matthias; Stroucken, Tineke; Meier, Torsten; Koch, Stephan W.; Zakharian, Aramis R.; Moloney, Jerome V. (Journal of the Optical Society of America B)
The optical properties of semiconductor quantum wells embedded in one-dimensional photonic crystal structures are analyzed by a self-consistent solution of Maxwell’s equations and a microscopic many-body theory of the material excitations. For a field mode spectrally below the photonic band edge it is shown that the optical absorption and gain are enhanced, exceeding by more than 1 order of magnitude the values of a homogeneous medium. For the photonic crystal structure inside a microcavity the gain increases superlinearly with the number of wells and for more than five wells exceeds the gain of a corresponding vertical-cavity surface-emitting laser.

Excitonic wave packet dynamics in semiconductor photonic-crystal structures - Pasenow, B.; Reichelt, Matthias; Stroucken, T.; Meier, Torsten; Koch, S. W. (Physical Review B)
Significant aspects of the light–matter interaction can be strongly modified in suitably designed systems consisting of semiconductor nanostructures and dielectric photonic crystals. To analyze such effects, a microscopic theory is presented, which is capable of describing the optoelectronic properties of such hybrid systems via a self-consistent solution of the dynamics of the optical field and the photoexcitations of the material. The theory is applied to investigate the local excitonic resonances, which arise as a consequence of the modified Coulomb interaction in the vicinity of a structured dielectric medium. The excitation of a coherent superposition of the spatially inhomogeneous optical transitions induces an intricate wave packet dynamics. In the presence of dephasing and relaxation processes, the coherent oscillations are damped and the photoexcited carriers relax into spatially inhomogeneous quasi-equilibrium distributions.

Microscopic Analysis of the Coherent Optical Generation and the Decay of Charge and Spin Currents in Semiconductor Heterostructures - Duc, Huynh Thanh; Meier, Torsten; Koch, S. W. (Physical Review Letters)
The coherent optical injection and temporal decay of spin and charge currents in semiconductor heterostructures is described microscopically, including excitonic effects, many-body Coulomb correlations, and the carrier LO-phonon coupling on the second-order Born-Markov level, as well as nonperturbative light-field-induced intraband and interband excitations. A nonmonotonic dependence of the currents on the intensities of the laser beams is predicted. Enhanced damping of the spin current relative to the charge current is obtained as a consequence of Coulomb scattering.

Gain and carrier losses of (GaIn)(NAs) heterostructures in the 1300–1550 nm range - Schlichenmaier, C.; Thränhardt, A.; Meier, Torsten; Koch, S. W.; Chow, W. W.; Hader, J.; Moloney, J. V. (Applied Physics Letters)
A microscopic model is used to analyze gain and loss properties of (GaIn)(NAs)∕GaAs quantum wells in the 1.3–1.55μm range, including Auger and radiative recombination. The calculations show that, as long as good material quality can be achieved, growing highly compressively strained samples is preferable due to their specific band structure properties. Optimum laser operation is possible slightly above a peak gain of 1000cm−1 ⁠.

Nonlinear optical response of the Si ( 111 ) − ( 2 × 1 ) surface exciton: Influence of biexciton many-body correlations - Oszwałdowski, R.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Rohlfing, Michael (Physical Review B)

COHERENT TRANSIENTS | Foundations of Coherent Transients in Semiconductors - Meier, Torsten; Koch, S.W. (Encyclopedia of Modern Optics)

Analysis of dilute nitride semiconductor laser gain materials in the 1.3-1.5/spl mu/m range - Meier, Torsten; Schlichenmaier, C.; Thränhardt, A.; Grüning, H.; Klar, Peter J.; Heimbrodt, Wolfram; Koch, S.W.; Chow, Weng W.; Hader, J.; Moloney, Jerome V. (Quantum Electronics and Laser Science Conference)
Theory/experiment comparisons of optical properties of dilute nitride heterostructures are presented. A type I - type II transition in In0.23Ga0.77As/GaNxAs1−x heterostructures is identified. The model is used for a study of lasing in the 1.3-1.5μm range.

Time-resolved photoluminescence of type-I and type-II (GaIn) As/Ga (NAs) heterostructures - Hantke, K.; Heber, J. D.; Schlichenmaier, C.; Thränhardt, A.; Meier, Torsten; Kunert, B.; Volz, K.; Stolz, W.; Koch, S. W.; Rühle, W. W. (Physical Review B)
A set of (Ga0.77In0.23)As/Ga(NxAs1−x) heterostructures is studied by time-resolved photoluminescence. Four samples with nitrogen concentrations from x=0.48% up to x=2.2% are investigated at different temperatures and with different excitation densities. The experiments suggest that the heterostructure band offset is type I for x=0.48% and type II for x=2.2%. The situation is more complex for x=0.72% and x=1.25%, since these samples are close to the transition from type I to type II. The experimental findings are analyzed using a detailed microscopic theory. Numerical calculations describe the measured data well. In particular, the interpretation of the experimental results concerning the band alignment is confirmed by the theoretical analysis.

Spatially inhomogeneous optical gain in semiconductor photonic-crystal structures - Reichelt, Matthias; Pasenow, B.; Meier, Torsten; Stroucken, T.; Koch, S. W. (Physical Review B)
The optical and electronic properties of semiconductor heterostructures in the vicinity of photonic crystals are discussed. The theoretical approach provides a self-consistent solution of the dynamics of the electromagnetic field and the material excitations. Due to the influence of the structured dielectric environment on the Coulomb interaction, the exciton resonances and the quasiequilibrium carrier densities in the spatially homogeneous semiconductor become space dependent. It is demonstrated that these inhomogeneities lead to distinct modifications of the optical absorption and gain spectra. As an application, numerically calculated density-dependent optical spectra are analyzed for an array of semiconductor quantum wires which are close to a two-dimensional photonic crystal. The spatial inhomogeneities result in novel excitonic absorption features and modification of the optical gain in these structures.

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Optical properties of semiconductor photonic-crystal structures: spatially-inhomogeneous excitonic resonances and optical gain - Meier, Torsten; Reichelt, Matthias; Pasenow, B.; Stroucken, T.; Koch, S.W. (2005 annual conference of the German Physical Society (DPG) during the World year of physics)

Semiconductor Optics in Photonic Crystal Structures - Meier, Torsten; Koch, Stephan W. (Photonic Crystals: Advances in Design, Fabrication, and Characterization)

Nonlinear optical properties of semiconductor quantum wells inside microcavities - Meier, Torsten; Sieh, C.; Koch, S.W.; Lee, Y.-S; Norris, T.B.; Jahnke, F.; Khitrova, G.; Gibbs , H.M. (Optical Microcavities)
Experimental results on the nonlinear optical properties of semiconductors are compared with microscopic calculations which include Coulomb many-body correlations at different levels. One aim of this chapter is to show that microscopic theories, which have been developed for bare semiconductor heterostructures, are also able to describe semiconductor microcavities very well. Therefore, there is no need to phenomenologically introduce polariton-polariton interactions and parametric scattering of cavity polaritons to describe microcavity experiments, but instead a fully microscopic theory based on a Fermionic electron-hole Hamiltonian can be used. The treatment of many-body correlations using the second-order Born approximation and the dynamics-controlled truncation scheme are introduced and analyzed for bare heterostructures. These approaches are able to successfully explain a number of important experimental results which originate from the dynamics of many-body correlations. Then measurements of the nonlinear optical properties of a quantum-well microcavity are described. In these experiments the spectrally- and temporally-resolved nonlinear optical response is studied in detail using a pump-probe geometry. In particular, the polarization and intensity dependencies of the spectral probe reflection changes and their temporal evolution are analyzed. The prominent features of these experiments are well accounted for by the microscopic many-body theory.

Fano resonances in metallic photonic crystals - Meier, Torsten; Giessen, H.; Linden, S.; Christ, A.; Kuhl, J.; Nau, D.; Thomas, P.; Koch, S.W. (Fano resonances in metallic photonic crystals)
We demonstrate that interference of optical excitations of regularly arranged metallic nanodots on a waveguide shows spectral signatures of Fano resonances. The reason is coupling of localized particle plasmons and waveguide modes with different electronic continua.

Onset of Dynamical Localization in a Semiconductor Superlattice - Meier, Torsten; Koch, M.; Ciulin, V.; Carter, S.G.; Sherwin, M.S.; Koch, S.W.; Zide, J.; Driscoll, D.; Gossard, A.C. (International Quantum Electronics Conference)
An excitonic blue-shift is observed when a GaAs/AlGaAs superlattice is irradiated with a strong THz field. This observation is compared with a microscopic calculation, and is consistent with the onset of dynamical localization.

Five-Wave-Mixing Spectroscopy of Ultrafast Electron Dynamics at a Si(001) Surface - Voelkmann, C.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Höfer, U. (Physical Review Letters)
The optically induced electron dynamics at a Si(001) surface is studied using a five-wave-mixing setup which measures the diffracted second-harmonic intensity induced by three ultrashort (13 fs) laser pulses. Depending on the time ordering of the pulses, this technique is capable of monitoring the temporal evolution of photoexcited one- or two-photon coherences, or populations. For a particular pulse sequence, the experiments show a delayed rise and a decay of the diffracted signal intensity on time scales of 50 and 250 fs, respectively. This response can be described by optical Bloch equations by including rapid scattering of the photoexcited carriers in the D(down)band of Si(001).

Nonequilibrium gain in optically pumped GaInNAs laser structures - Thränhardt, A.; Becker, S.; Schlichenmaier, C.; Kuznetsova, I.; Meier, Torsten; Koch, S. W.; Hader, J.; Moloney, J. V.; Chow, W. W. (Applied Physics Letters)
A theory is presented which couples a dynamical laser model to a fully microscopic calculation of scattering effects. Calculations for two optically pumped GaInNAs laser structures show how this approach can be used to analyze nonequilibrium and dynamical laser properties over a wide range of system parameters.

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Meier, Torsten; Varga, I.; Thomas, P.; Koch, S.W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect and spectral oscillations of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (Physical Review B)
A microscopic approach is presented to compute nonlinear optical properties of semiconductor surfaces. The method uses quasiparticle wave functions and dispersions obtained from ab initio band-structure theory as an input for Bloch equations which describe the optical properties. Excitonic effects in the linear absorption spectra of the Si(111)- (2×1) surface are obtained by integrating equations of motion. To demonstrate the applicability of the approach for analyzing nonlinear optical properties, ultrafast light-intensity-dependent absorption changes of the surface exciton are predicted. The numerical results discuss the optical Stark effect and spectral oscillations of the surface exciton which can both be observed in pump-probe experiments.

Signatures of biexcitons and triexcitons in coherent non-degenerate semiconductor optics - Meier, Torsten; Sieh, C.; Finger, E.; Stolz, W.; Rühle, W.W.; Koch, S.W.; Thomas, P. (physica status solidi (b))
Signatures of exciton and two-exciton states in semiconductor systems are investigated experimentally and theoretically. A set of quantum well samples with different well widths is studied using coherent excitation spectroscopy. The experimental results are analyzed using a microscopic model demonstrating the importance of biexciton correlations and disorder effects. Additional numerical investigations of absorption changes in small nanorings are employed to analyze optical transitions from two-exciton to three-exciton resonances.

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Varga, Imre; Thomas, Peter; Meier, Torsten; Koch, Stephan W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Electronic transport in a one-dimensional random array of scatterers - Meier, Torsten; Filinov, V.S.; Thomas, P.; Varga, I.; Bonitz, M.; Fortov, V.E; Koch, S.W. (Journal of Physics A: Mathematical and General)
The quantum dynamics of an ensemble of interacting electrons in an array of random scatterers is treated using a new numerical approach for the calculation of average values of quantum operators and time correlation functions in the Wigner representation. This approach combines both molecular dynamics and Monte Carlo methods and computes numerical traces and spectra of the relevant dynamical quantities such as momentum–momentum correlation functions and spatial dispersions. Considering, as an application, a system with fixed scatterers, the results clearly demonstrate that the many-particle interaction between the electrons can lead to an enhancement of the conductivity at intermediate densities.